2015
DOI: 10.1089/adt.2015.634
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Time-Dependent Distribution of Rifampicin in Rat Brain Using MALDI MSI and Quantitative LCMS/MS

Abstract: Rifampicin (RIF) is a major component for short-course chemotherapy against tuberculosis, since it is active against rapidly metabolizing as well as dormant bacteria. According to the Lipinski rules, RIF should not enter the blood-brain barrier. Visualization of tissue drug distribution is of major importance in pharmacological studies; thus, far imaging of RIF in the brain has been limited to positron emission tomography. We propose using matrix-assisted laser desorption/ionization mass spectrometry imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 92%
“…Matrix assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) is a label‐free technique, which offers the advantage of determining the distribution of parent drug and metabolites simultaneously . We have recently shown that a combination of liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with MALDI MSI provides better correlation than PET imaging technique . The aim of this study was to establish methods for the preclinical evaluation and localization of fluoroquinolones in the rat brain by using LC‐MS/MS and MALDI MSI as sensitive tools for its determination.…”
Section: Introductionsupporting
confidence: 92%
“…Using this information, we propose that pretomanid is able to diffuse into the neighbouring lateral ventricles and follows the rostral migratory stream to the olfactory area leading to the observed reduction in drug distribution after 120 min in the CC. The findings we have presented in this article together with previous reports indicate that the distribution and localisation of drugs in the brain vary among different groups of antibiotics depending on their structural and chemical properties (Liu et al, 2010;Mindermann et al, 1993;Shobo et al, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…1 In the most recent TB drug pipeline, there are several novel agents, many of which are currently undergoing clinical trials to determine their potential against TB. [2][3][4][5][6][7][8] Amongst them, BDQ has proven to be a promising rst-in-class US FDA approved anti-TB agent, which belongs to the diarylquinoline class of antibiotics. BDQ is proposed for the treatment of multidrugresistant tuberculosis (MDR-TB) in combination with other active anti-TB drugs, when an effective therapy regimen could not be established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group studied the localization and bio-distribution of TB drugs (clofazimine, linezolid, rifampicin, pretomanid, TBA-354) in the rodent brain. [2][3][4]6,7,22 However, these drugs offer partial protection in the CNS, thus further improvements in TB chemotherapy is required. 3,4 At present, limited data is available on the localization and distribution of BDQ in the brain.…”
Section: Introductionmentioning
confidence: 99%